Differences in the Organisation of Apprenticeship in Europe: findings of a comparative evaluation study - Rauner, Felix [Verfasser]; Wittig, Wolfgang [Verfasser] (My University, 2010)
"This article presents a comparative analysis of governance structures in the dual vocational education and training (VET) systems of Austria, Denmark, Germany and Switzerland. First a theoretical framework for the classification of plural systems such as dual apprenticeship training is discussed. It is argued that governance in VET can be described according to the coherence of the system on the one hand and the rationale of agency on the other. Moreover, it is assumed that four ideal types of governance can be distinguished. A methodology is presented to implement this framework in data collection and analysis and as an evaluation tool for expert workshops. The study recommends a consistent legal framework regarding the cooperation of learning venues and the establishment of an evaluation and feedback scheme in the shape of an assessment during the training process. In order to efficiently coordinate VET practice, VET policy and VET research, the establishment of a 'VET innovation system' is suggested." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3 Steuerung; S 1.3.1 Ausbildung im Dualen System; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.1 Deutschland; I 2.2.1 Westeuropa; Bildungssteuerung; Duales System; Effizienz; Evaluation; Bildungsmonitoring; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Österreich; Schweiz